Flexible Bistable Smectic-A Liquid Crystal Device Using Photolithography and Photoinduced Phase Separation. (31st October 2012) - Lu, Yang; Guo, Jinbao; Wang, Hao; Wei, Jie
Abstract : A flexible bistable smectic-A liquid crystal (SmA LC) device using pixel-isolated mode was demonstrated, in which SmA LC molecules were isolated in pixels by vertical polymer wall and horizontal polymer layer. The above microstructure was achieved by using ultraviolet (UV) photolithography and photoinduced phase separation. The polymer wall was fabricated by photolithography, and then the SmA LC was encapsulated in pixels between polymer wall through UV-induced phase separation, in which the polymer wall acts as supporting structure from mechanical pressure and maintains the cell gap from bending, and the polymer layer acts as adhesive for tight attachment of two substrates. The results demonstrated that all the intrinsic bistable properties of the SmA LC are preserved, and good electrooptical characteristics such as high contrast ratio and excellent stability of the bistable states were characterized. This kind of SmA bistable flexible display has high potential to be used as electronic paper, smart switchable reflective windows, and so forth.